Information technology and new horizons in engineering pedagogy: quiz establishment in large-scale classes - Rahnamayiezekavat, Payam; Bernold, L. (2013)
Examination is a key component of education. Quizzes can motivate students to be prepared in advance, and encourage them to accompany the lecturer in the teaching. This is a tool applicable for managing crowded classrooms. But designing and establishing quizzes in high circulation is the main obstacle in their vast application. Internet as part of today’s modern life is a foundation to overcome this limit. Universities as pioneer applicants of internet have already installed its infrastructure. Although everybody agrees that information technology (IT) is effective in education, unfortunately due the lack of demonstration and scientific evaluation of its capabilities, it is not adopted in current practice. Following an effective learning paradigm, this article surveyed “Simultaneous Electronic Response System” and assessed its applicability to involve engineering students in learning especially by establishing large-scale online quizzes. Results confirmed the system’s performance and registered improved learning.